THE FAMILY ROLE IN THE EDUCATIONAL PROCESS IN COLOMBIA - Doris Rocio Salamanca; Claudia Patria Bonett Quintero; Martha Judith Jaimes Mogollon (LÍNEA IMAGINARIA, 2025)
This research aims to analyze the role of the family in the educational process in Colombia. Schools will always be seen as forging generations, with individuals capable of playing a leading role in society. Therefore, it is essential that students’ experiences be aligned with pedagogical processes, delegating this to educational institutions, teachers, and parents and guardians. But the most important factor is the family, where true formation in values ​​and principles takes place. The home is our first school. The lack of family participation sometimes leads children to feel hesitant when making decisions. The role of teachers is integral to the knowledge imparted through curricula created for such formations and appropriate for the students’ ages. Education is too important to be left solely in the hands of teachers. Therefore, the participation of parents and families, working hand in hand with teachers, the institution, and the community, is imperative, ensuring a better life for our students.